Focusing on the nuclear and subnuclear dynamics of light and circadian signalling. (16th August 2019) - Ronald, James; Davis, Seth J.
Abstract: Circadian clocks provide organisms the ability to synchronize their internal physiological responses with the external environment. This process, termed entrainment, occurs through the perception of internal and external stimuli. As with other organisms, in plants, the perception of light is a critical for the entrainment and sustainment of circadian rhythms. Red, blue, far‐red, and UV‐B light are perceived by the oscillator through the activity of photoreceptors. Four classes of photoreceptors signal to the oscillator: phytochromes, cryptochromes, UVR8, and LOV‐KELCH domain proteins. In most cases, these photoreceptors localize to the nucleus in response to light and can associate to subnuclear structures to initiate downstream signalling. In this review, we will highlight the recent advances made in understanding the mechanisms facilitating the nuclear and subnuclear localization of photoreceptors and the role these subnuclear bodies have in photoreceptor signalling, including to the oscillator. We will also highlight recent progress that has been made in understanding the regulation of the nuclear and subnuclear localization of components of the plant circadian clock. Abstract : Photoreceptors can associate to subnuclear structures to initiate signalling. Similarly, many interacting clock proteins also exist in distinct subnuclear structures in a time‐dependent manner. In this review, we highlight recent advances made in understanding the mechanisms facilitating their nuclear and subnuclear localization.